Ön Açık Kapanışın İskeletsel Boyutu - Yahya Tosun; Ali Vehbi Tuncer; Şule Tosun (Galenos Yayinevi, 1991)
In the field of orthodontics it is known that the treatment of cases wit anterior open bite especially those presenting a vertical growth pattern, is rather hard. Fc this reason, determination of the true nature of this abnormality and a proper diagnosi and treatment planning is utmost important. The aim of this study is twofold: 1-T determine the frequency of skeletal open bite tendency in anterior open bite cases using cephalometric parameters. 2-To evaluate the relationship between parameters Cephalometric analysis of 50 anterior open bite cases showed that more than the half c the cases presented a skeletal open bite tendency when SN-MP, PFH/AFH and PP-M measurements were used. A correlation analysis showed a significant statisticc relationship between SN-MP and PFH/AFH parameters.